Theoretical scheme of a SPEL based sectorial settlement system and consistency controlled forecasts - Bunkóczi, László (Acta Agraria Kaposváriensis, 2010)
The paper approaches on one hand from the existing agricultural sector models in creating a unified settlement frame system for all sectors, and on the other hand in the terms of preparation for the future – to create an authentic or better a more authentic future description. Nowadays as KSH (Central Statistical Office) reported the agricultural sector down to 2% in GDP, the need for settling the agricultural sectors value adding ability from real data is increased high and thus a SPEL based scheme would be reasonable, as not only the financial part of the problem than, the material movements within farms, within country and export import could be pathed. The valid future picture part of the paper tries to show that simple, accepted and wide range used forecsting methods (eg.: linear trend) could be good enough, if the inner and outer parts of the given phenomena are in tight accord.